Implementation of Guided Inquiry Learning Model Based Blended Learning to Train Creative Thingking Skill of Eleventh Grade Students in The Factors that Affect of Chemical Equilibrium - Firyal Nabilah Qurrotu Aini; Ismono Ismono (Universitas Lampung, 2020)
Abstract: Implementation of Guided Inquiry Learning Model Based Blended Learning to Train Creative Thinking Skill of Eleventh Grade Students in the Factors that Affect of Chemical Equilibrium. This study aims to improve students' creative thinking skill in the factor that effect of chemical equilibrium using student learning outcomes towards the implementation of learning model as an online learning solution, to know the implementation, student activities and to know student responses toward learning model. Collect the data methods used questionnaires, observation, and test methods. The results implementation of learning gets a percentage of 90% which is categorized as very good. Student activities when given a learning model to practice creative thinking skills get 24.4% in the Fluency, 26.9% in the Flexibility and 12.7% of the student activity time was used to practice Elaboration. Student creative thinking skill uses the One-Group Pretest-Posttest Design, the results obtained by students increase from the comparison of the pretest and posttest, and the results tested in gain score with an average result is ≥ 0.7 or high category. Students give a positive response of 95.3% to the guided inquiry learning model based on blended learning on the factors that affect chemical equilibrium. Keywords: Blended Learning, Guided Inquiry, Creative Thinking Skill, Chemical Equilibrium.